Contested heritage in Europe and Africa
1 online resource.
Keywords: "This book investigates Euro-African cultural relations, considering their connected histories through material and immaterial forms of representation, commemoration, and memorialization. Recent waves of protest around the world have called for restitution of looted African art, and toppled statues and vandalized monuments which are connected to white suprematism, colonialism, and imperialism. These events have highlighted an urgent need to debate the management and preservation of Europe and Africa's shared heritage. Drawing on a range of varied, trans-continental case studies, this book considers the key question of whether such monuments should be removed as forms of unacceptable celebration of an evil past, or preserved precisely because of what they recount about that past of oppression and domination. The book encourages readers to consider how diverse and pervasive the notions of shared heritage and common past are, encompassing discussions of statues, exhibitions, graffiti, tapestries, and commemorations. Providing a timely analysis of the developing cultural relations between Africa and Europe, this book will be an important resource for researchers across the fields of global history, heritage studies, memory studies, and international relations"--